1992
DOI: 10.1111/j.1365-2559.1992.tb00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammary hamartoma—a review of 35 cases

Abstract: Mammary hamartomas are macroscopically well-delineated tumours composed of a variable mixture of epithelial elements, fat and fibrous tissue. Such lesions are an under-recognized entity and, as they can be visualized by mammography, may be seen more frequently with the advent of the UK National Breast Screening Programme. The clinical and pathological features of 35 cases of mammary hamartoma seen at the Imperial Cancer Research Fund Clinical Oncology Unit at Guy's Hospital between 1979 and 1990 have been revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 11 publications
8
91
1
3
Order By: Relevance
“…However, on macroscopic examination, hamartomas are typically well-circumscribed, lenticular, round or oval masses with heterogeneous features on cut section, depending on the particular prominence of histological components, mainly white and⁄or pinkish, with yellow islands. [11,12,13,14] These features were also noted in the present study.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, on macroscopic examination, hamartomas are typically well-circumscribed, lenticular, round or oval masses with heterogeneous features on cut section, depending on the particular prominence of histological components, mainly white and⁄or pinkish, with yellow islands. [11,12,13,14] These features were also noted in the present study.…”
Section: Resultssupporting
confidence: 86%
“…This feature was noted in 55.5% of cases in the present study which was consistent with the rates reported in literature. [7,9,11] Cystic changes and apocrine metaplasia were noted in more than 50% of cases in our study. However this feature was observed to a lesser extent by few other authors.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…On the other hand I am glad to see that a cautious approach to the premature concept of lobular intraepithelial neoplasia (LIN) and ductal intralobular neoplasia (DIN) was adopted. The concept is, in theory, attractive but until the various and probably multiple lines of breast cancer evolution are more clearly identified, this concept must remain in cold storage.In other areas apparent consensus in the book is not matched by reality; the section on mucinous cystic lesions associated with pseudomyxoma peritonei rather oversimplifies what remains a still contentious area of pathology.The pattern of referencing in the text was to a certain extent patchy and didn't include some of the original descriptions of many lesions, for example the co-incidence of mammary hamartoma and pseudoangiomatous stromal hyperplasia [3]. These oversights no doubt relate to the idiosyncratic knowledge of the literature, which many specialist histopathologists have.…”
mentioning
confidence: 99%
“…Findings by Hartveit showed that the ultrastructure of attenuated lymphatic endothelial cells form sheets rather than vessels within the breast stroma and that these potential spaces form the missing lymphatic system of the breast, the lymphatic labyrinth (4,5). Fisher et al concluded that PASH and this lymphatic labyrinth (spaces ultrastructurally lined by slender cells with tapering cytoplasmic processes that are either fibroblasts or lymphatic endothelial cells) are related structures (6). Recently, Asioli et al, in a three-dimensional study of two cases of normal breast tissue and one case of PASH, demonstrated direct anastomoses between pre-lymphatic channels and true lymphatics of the breast (2).…”
Section: Discussionmentioning
confidence: 99%